2019
DOI: 10.3389/fonc.2019.01107
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs. Open Abdominal Radical Hysterectomy for Cervical Cancer: A Single-Institution, Propensity Score Matching Study in China

Abstract: Study Objective: To compare the surgical and oncologic outcomes between open abdomen radical hysterectomy (ARH) and laparoscopic radical hysterectomy (LRH) for cervical cancer.Methods: Retrospective observational study with propensity score matching was used to ensure balanced groups for ARH and LRH. One-hundred-and-ninety-eight women with cervical cancer, 99 treated using ARH and 99 using LRH, between January 2012 and December 2014. Outcomes included disease-free survival (DFS), overall survival (OS), intra-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 33 publications
0
39
0
2
Order By: Relevance
“…After reviewing the full text of the remaining 77 articles, we included 36 articles in the final analysis (41)(42)(43)(44)(45)(46). Forty studies were excluded from the final review ; they had no available survival outcome data (N = 19).…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the full text of the remaining 77 articles, we included 36 articles in the final analysis (41)(42)(43)(44)(45)(46). Forty studies were excluded from the final review ; they had no available survival outcome data (N = 19).…”
Section: Literature Searchmentioning
confidence: 99%
“…Study design Matched 10 (5,11,13,15,16,19,28,30,41,43) 1.49 (1.19-1.88) 0.001 27.5 Fixed effect Retrospective 26 (6-10, 12, 14, 17, 18, 20-27, 29, 31-34, 42, 44-46) 1. (12,13,19,23,24,(27)(28)(29)(30)(31)(32)(33)(34)(42)(43)(44)(45)(46) 1. Small (at least one arm < 90) 18 (5-11, 14-18, 20-22, 25, 26, 41) 0.90 (0.67-1.20)…”
Section: Fixed Effectmentioning
confidence: 99%
“…Laparoscopic radical hysterectomy (LRH) was shown to have more favorable short-term outcomes than open surgery, including less blood loss, lower transfusion rates, shorter operative times and hospital stays, and fewer postoperative complications ( 10 14 ). Several retrospective studies also showed that LRH and ARH have equivalent progression-free survival (PFS) and overall survival (OS) rates ( 11 , 15 , 16 ). LRH has been gradually accepted as a reasonable alternative to ARH for patients with early-stage cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, their efforts to assess how manipulator use and vaginal closure may modify the magnitude of the associations between minimally invasive hysterectomy and adverse survival outcomes is an important step in elucidating the factors that may mediate these effects. While some recent well-designed observational studies have not found an association between minimally invasive radical hysterectomy and recurrence or death, 17 18 the majority of such studies [6][7][8][9][10][11][12][13][14][15] have found evidence of harm. The SUCCOR study delivers another significant blow to a surgical paradigm that is increasingly difficult to justify in routine clinical practice.…”
mentioning
confidence: 99%
“…[2][3][4][5] In addition to LACC, these guidelines have cited a growing literature of adequately powered, well-designed observational studies that, overall, have had concordant results. [6][7][8][9][10][11][12][13][14][15] In this issue of the International Journal of Gynecological Cancer, Chiva and colleagues 16 present additional evidence of the deleterious effect of minimally invasive radical hysterectomy, and suggest possible mechanisms underlying this association. The SUCCOR study is a large, retrospective, observational cohort study that evaluates associations between surgical approach and survival outcomes among women with International Federation of Gynecology and Obstetrics (FIGO) 2009 stage 1B1 cervical cancer within 126 institutions in 29 European countries.…”
mentioning
confidence: 99%